Implementation of Islamic Parenting: Collaboration between Community Service Program and Schools in Enhancing the Role of Parents Based on the Qur'an and Hadith - Alifia Nurshadrina Hermawan; Fakhra Tabqiya Rahman; Fuji Amanda; Levina Fauziyah Febriana; Rifqi Naufal Sidiq; Siti Muslikah (UIN Sunan Gunung Djati Bandung, 2026)
This study examines the implementation of Islamic parenting as a strategy to strengthen the role of parents in children’s education through collaboration between Community Service Program (KKN) students and schools. Islamic parenting is defined as a value-based approach rooted in moral, spiritual, and educational principles, positioning parents as the child’s first school. The study adopts the SISDAMAS (Participatory Community Development System) approach, which emphasizes community involvement in all stages of planning, implementation, and evaluation. The research site was TK Al-Kamilah, RW 08 Dusun 3, Kampung Bojong, Mekarsari Village, involving parents, teachers, KKN students, and local leaders. Findings indicate that the Islamic parenting seminar successfully enhanced parents’ awareness and skills in child-rearing, strengthened collaboration between families and schools, and produced Qur’an- and Hadith-based parenting modules that can be used continuously. The main challenges identified were parents’ limited understanding, the influence of digital media, and time constraints in conducting effective parenting practices. Practical implications suggest the need for regular parenting forums, mentoring programs for young families, and the integration of parenting initiatives into official village development agendas. This study contributes theoretically by integrating 21st-century parenting theories with Islamic parenting principles, and practically by offering a collaborative model that strengthens the role of families in children’s education.